A study on performance of V-slot shapes on rectangular patch antenna - Sahadah, Ahmad; Hazila, Othman; Dayang Khadijah, Hamzah; Hazila, Othman; Hasnah, Ahmad (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/